Prognostic significance of lymphovascular space invasion in low-risk endometrial cancer. Issue 3 (March 2019) - Ayhan, Ali; Şahin, Hanifi; Sari, Mustafa Erkan; Yalçin, Ibrahim; Haberal, Ali; Meydanli, Mehmet Mutlu
Abstract : Objective: The purpose of this study was to assess the prognostic significance of lymphovascular space invasion in women with low-risk endometrial cancer. Methods: A dual-institutional, retrospective department database review was performed to identify patients with 'low-risk endometrial cancer' (patients having <50% myometrial invasion with grade 1 or 2 endometrioid endometrial cancer according to their final pathology reports) at two gynecologic oncology centers in Ankara, Turkey. Demographic, clinicopathological and survival data were collected. Results: We identified 912 women with low-risk endometrial cancer; 53 patients (5.8%) had lymphovascular space invasion. When compared with lymphovascular space invasion-negative patients, lymphovascular space invasion-positive patients were more likely to have post-operative grade 2 disease (p<0.001), deeper myometrial invasion (p=0.003), and larger tumor size (p=0.005). Patients with lymphovascular space invasion were more likely to receive adjuvant therapy when compared with lymphovascular space invasion-negative women (11/53 vs 12/859, respectively; p<0.001). The 5-year recurrence-free survival rate for lymphovascular space invasion-positive women was 85.5% compared with 97.0% for lymphovascular space invasion-negative women (p<0.001). The 5-year overall survival rate for lymphovascular space invasion-positive women was significantly lower than that of lymphovascular space invasion-negative women (88.2% vs 98.5%, respectively; p<0.001). Age ≥60 years (HR 3.13, 95% CI 1.13 to 8.63; p=0.02) and positive lymphovascular space invasion status (HR 6.68, 95% CI 1.60 to 27.88; p=0.009) were identified as independent prognostic factors for decreased overall survival. Conclusions: Age ≥60 years and positive lymphovascular space invasion status appear to be important prognostic parameters in patients with low-risk endometrial cancer who have undergone complete surgical staging procedures including pelvic and para-aortic lymphadenectomy. Lymphovascular space invasion seems to be associated with an adverse prognosis in women with low-risk endometrial cancer; this merits further assessment on a larger scale with standardization of the lymphovascular space invasion in terms of presence/absence and quantity.